EXPLORING THE POTENTIAL OF CHATGPT AS A TECHNOLOGY-BASED TOOL FOR ARABIC LANGUAGE LEARNING: BENEFITS AND RISKS - Berliani, Denitia; Azhari, Irsad; Taufiqurrochman, R. (Kitaba, 2024)
This research aims to explore the potential for using ChatGPT as a tool in technology-based Arabic language learning, focusing on identifying the advantages and risks of its use. This research was conducted in response to the increasing use of artificial intelligence in education, especially in Arabic language learning. The research method used is a literature study with a desk research approach, namely exploring data from empirical and relevant research. The research results show that ChatGPT has great potential as a tool for learning Arabic. Key benefits include its ability to improve writing skills, facilitate discussions, and provide quick responses. The risks of using ChatGPT are excessive dependency, the potential for academic cheating, and a negative impact on critical and analytical thinking skills. This research emphasizes the importance of careful and wise regulations in using ChatGPT as a tool in the Arabic language learning process.